2021
DOI: 10.1111/iju.14603
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy‐assisted puncture for ultrasonography‐guided renal access significantly improves overall treatment outcomes in endoscopic combined intrarenal surgery

Abstract: Objectives: To assess the impact and availability of ureteroscopy-assisted puncture for percutaneous renal access during ultrasonography-guided miniaturized (mini)-endoscopic combined intrarenal surgery for large volume renal and/or proximal ureteral stones. Methods: We conducted a multi-institutional retrospective cohort study for urolithiasis treatment. Data from a total of 313 patients who underwent mini-endoscopic combined intrarenal surgery to treat renal and/or ureteral stones between January 2016 and Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Recently, a number of works have appeared that offer to perform percutaneous access to the kidney under the visual guidance of a flexible ureterorenoscope, inserted into the target calyx. Thus, K. Taguchi et al [51] compared the results of percutaneous access to the kidney during ECIRS between two groups of patients: Group 1 (n = 126) -percutaneous access under ultrasound guidance with ureterorenoscopic imaging from the middle of the renal cavity system and Group 2 (n = 187) -traditional percutaneous access only under ultrasound guidance. In their work, the authors showed that puncture of the calyx-pelvic system (CPS) under combined ultrasound and ureterorenoscopic guidance was associated with a lower risk of additional surgery (OR = 0.31; P = 0.011), reducing the number of postoperative infectious complications (OR = 0.34; P = 0.003), the total duration of the procedure (less by 11 minutes; P = 0.011), radioscopy (less by 3 minutes; P = 0.034) and the duration of postoperative ureteral stenting (less by 8 days; P = 0.011).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a number of works have appeared that offer to perform percutaneous access to the kidney under the visual guidance of a flexible ureterorenoscope, inserted into the target calyx. Thus, K. Taguchi et al [51] compared the results of percutaneous access to the kidney during ECIRS between two groups of patients: Group 1 (n = 126) -percutaneous access under ultrasound guidance with ureterorenoscopic imaging from the middle of the renal cavity system and Group 2 (n = 187) -traditional percutaneous access only under ultrasound guidance. In their work, the authors showed that puncture of the calyx-pelvic system (CPS) under combined ultrasound and ureterorenoscopic guidance was associated with a lower risk of additional surgery (OR = 0.31; P = 0.011), reducing the number of postoperative infectious complications (OR = 0.34; P = 0.003), the total duration of the procedure (less by 11 minutes; P = 0.011), radioscopy (less by 3 minutes; P = 0.034) and the duration of postoperative ureteral stenting (less by 8 days; P = 0.011).…”
Section: Resultsmentioning
confidence: 99%
“…From the very first article in 2008 reporting that ECIRS in GMSV position in their 127 patients yielded excellent single-step SFR with minimal complications and unquestionable anaesthesiologic advantages [1], their results have been time tested and repeatedly verified as seen in multiple stated studies above [8,10,14 ▪ ,18 ▪▪ ,23 ▪▪ ,24,25 ▪▪ ,26,34,36]. Indeed, this is evident from the fact that ECIRS is now being performed in multiple positions with miniaturized and single access and even under ultrasound guidance.…”
Section: Discussionmentioning
confidence: 97%
“…The remaining 162 full-text articles were further evaluated for appropriateness and 127 articles were excluded. Finally, 35 articles were considered eligible and included [1,2 ▪ ,6–13,14 ▪ ,15–17,18 ▪▪ ,19 ▪ ,20–22,23 ▪▪ ,24,25 ▪▪ ,26–36,37 ▪ ,38]. Figure 1 shows the flow diagram of the literature search.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations